XVIII. yüzyıl osmanlı toplumunda nazari ve tatbiki olarak karz işlemleri - Kaya, Süleyman (My University, 2007)
XVIII. YÜZYIL OSMANLI TOPLUMUNDA NAZARİ VE TATBİKİ OLARAK KARZ İŞLEMLERİ İnsanoğlunun toplumsal yaşamda borç alma ihtiyacı duyduğu bilinen bir gerçektir. Bu durum tarihin hemen her devrinde borç vererek faiz geliri elde etmeği meslek edinen şahıs veya kurumların ortaya çıkmasına sebebiyet vermiştir. Ancak ilahi dinlerin tamamında faiz yasak kılınmıştır. İslam’a bağlı kalmayı kendilerine şiar edinmiş Osmanlı ulemasının da faizi açık ve kesin ifadelerle yasakladıkları görülür. Buna mukabil toplumun borç alma ihtiyacını karşılamak üzere bazı hile-i şeri‘yyelere ulema tarafından cevaz verildiği müşahede edilir. 18. yüzyıl söz konusu olduğunda muamele-i şeri‘yye ve bey bi’l-istiğlâl en çok uygulanan hile-i şeri‘yyelerdir. Bu işlemlerle A’dan Z’ye her şahıs ve kurum, verdikleri borç karşılığında %15’i geçmemek şartıyla artı bir gelir elde edebilirdi. Verilen borç karşılığında artı bir fazlalık alma, sömürü aracı olarak dönüşmeye yatkındır. Bu noktada ulemanın, muamele-i şeri‘yye, bey bi’l-istiğlâl vb. işlemleri hem sömürü aracına dönüşmesini engelleyecek şekilde düzenledi hem de denetim altında tuttuğu görülür. Temel işlevi devlet maliyesi ve askeri zümrenin kredi ihtiyacını karşılamak olan sarrafların sair kurum ve şahıslara da borç verdiği görülür. Vakıfların borç verdiği kimseler ise daha ziyade esnaf ve hane halklarıdır.

PRACTICES OF KARDH IN THE EİGHTEENTH CENTURY OTTOMAN SOCIETY FROM A THEORETICAL AND PRACTICAL PERSPECTIVE It is a well known fact that individual human beings occasionally feel the need to borrow in social life. This state of affairs has let to the emergence of individuals and institutions in every epoch of history professionalizing in the field of lending money on the basis of some interest revenue. However, receiving interest was banned by all monotheist religions. Accordingly, it was observed that the Ottoman Ulema, renown with their strict loyalty to Islamic principles, have banned all forms of interest with clear and unambiguous statements. However, it was also observed that certain deviations from religious teachings (hila-i shari‘yye) were legitimized by the Ulema in order to meet the rising borrowing needs of the society. As far as developments in the 18th century are concerned, “muamala-i shari‘yye” and “bay bi’l-istiglâl” constituted the most commonly applied forms of such deviations legitimized with religious references. Through these practices, every individual and institution from A to Z could have acquired a surplus income up to but not exceeding 15% of the original amount extended in lending arrangements. It is conceivable that the practice of receiving a surplus on the basis of the lent amount could easily turn into a means of exploitation. On this point, it appears that the Ulema had kept practices such as “muamale-i shari‘yye”, bay bi’l-istiglâl etc. under control and regulated them to prevent their transformation into means of exploitation. It was also observed that the jewelers, whose main function was to meet the credit requirements of public treasury and military personnel, were also involved in lending arrangements to other individuals and institutions. The endowments (waqf), on the other hand, were providing credits particularly to small business and shop owners as well as households.
Keywords: İslam Hukuku; Osmanlı İmparatorluğu, 1299-1918_Borçlar_İslam Hukuku